A comprehensive model of blood flow restriction in the postsurgical rat - Andin Fosam; Susana Castelo Branco Ramos Nakandakari; Isabella Chavez Miranda; Christopher Taber; Julie O'Connell; Andrew Raines; Yuichi Ohashi; Hualong Bai; Alan Dardik; Christina Allen; Rachel J. Perry (Physiological Reports)
Abstract The mechanisms underlying blood flow restriction with low‐load exercise (BFR‐exercise)‐mediated muscle hypertrophy are not well understood. Lack of standardized rodent models of BFR‐exercise likely contributes to this gap. We demonstrate in male rats a comprehensive, clinically relevant protocol that generates a muscle loss state via bilateral anterior cruciate ligament reconstruction, achieves targeted, external blood flow occlusion, and performs weighted hind‐limb isolating knee extension exercise with BFR. These methods can be applied to mechanistic and physiologic studies of BFR‐exercise.